Telepractice in the context of the COVID-19 pandemic: Analysis of adaptations and perceptions of speech and language therapists - Massana, Cèlia; Figueroa, Mario (Revista de Investigación en Logopedia, 2022)
Telepractice in Speech-Language therapy facilitates services in exceptional situations such as COVID-19 pandemic. Due to the restrictions imposed, speech-language pathologists (SPL) have had to adopt new approaches in their professional practice. The aim of this study is, through an online survey, to analyse the perception and the assessment of Spanish SPL about telepractice, to describe the adaptation and to identify the possible problems that have emerged. The survey was answered by thirty-seven active speech therapists. The results show that the majority of respondents have used telelogopedia (75.6%) and that their appreciation about it has increased since the beginning of the pandemic. Only one of the participants had received telelogopedia training and two had used telelogopedia before the pandemic. The main reason given by the SPL for not using telepractice sessions was related to patient typology and/or age inappropriateness. The main disadvantages of the use of telelogopedia are identified and proposals for clinical practice are exposed.